(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The term ’tale in verse’ strictly taken includes the entire field of English poetry narrative or epic in kind. The tale in its present form is ’told’, but the telling is after the same fashion as the talk of Shakespeare’s men and women. A satirical tale like Absalom and Achitophel, or a burlesque like the Rape of the Lock, or an allegory like the Faery Queen are less pure forms of the tale than simple narratives. The aim of the verse tales is not to teach a moral through satire or burlesque but to entertain us with a narrative where the events and individuals, whether ordinary or extra-ordinary are yet in the scale of common life. In order to understand the nature of a verse-tale, we describe here the essentials of it. It stirs the imagination of the readers and appeases their love of beauty, romance, adventure, chivalry and heroism. A pure verse tale is clear, straight forward and smooth in flow.It has clear comprehension of events. It mostly narrates a brave and noble deed. The story is the most important factor, and the story should be clear. The ideal poem—–is that which tells a fine story finely, sets forth a brave tale in stirring words.